BRIEF HISTORY OF THE FIEP CHILE (Fiep Bulletin - online, 2013)
ABSTRACT: the history of the FIEP CHILE Committee dates back to the end of 1889, when Mr. JOAQUIN CABEZAS GARCIA, a young Chilean Elementary School teacher, went to Sweden for his first studies on Manual Works and Gymnastics with the famous professor Luys. Later, he went back to Sweden several times and, in one of them, in 1918, he got to know and committed himself to the International Federation of Gymnastics Ling. This way, in 1923, during the creation of the Gran Movimiento, authorities of the International Federation communicated his incorporation as an active member. Another opportunity for Cabezas, was his visit to the 1st LINGIADA, in 1939. History goes on with Mr. Luis Bisquertt Susarte, who attends the 2nd LINGIADA in 1949, where he gets totally committed to the whole FIEP Movement, thus transcribing in the Chilean Magazines of Physical Education, during almost three years, one by one, all of the events (conferences, meetings, presentations, visits) which characterized this second event in homage to Gran Per Henrik LING. After coming back, besides publicizing the LINGIADA, Dr. Bisquertt constitutes the First FIEP-CHILE COMMITTEE, 1950. After Cabezas' and Bisquertt's experiences, the following professors take on responsibility for the CHILE Committee: Alberto Palma; Rosauro Salas; Antonio Losada; Milton Cofre; Sergio Guarda and Horacio Lara. This period and the CHILE Committee are finished with the issuing of the year 2000 Manifesto, a task taken over by Professor Sergio Guarda Echeverry, Director of the “EDUCACION FISICA –CHILE” magazine. So we could say that regarding the Physical Education Magazine, FIEP is also being referred to, because there's hardly an issue in which an article, a note or news from the Federation are not included, whether in Chile or in other countries.